Histone deacetylase inhibition reduces cardiac connexin43 expression and gap junction communication - Xu, Qin; Lin, Xianming; Andrews, Laura; Patel, Dakshesh; Lampe, Paul D.; Veenstra, Richard D. (Frontiers in Pharmacology, 2013)
Histone deactylase (HDAC) inhibitors are being investigated as novel therapies for cancer, inflammation, neurodegeneration, and heart failure. The effects of HDAC inhibitors on the functional expression of cardiac gap junctions (GJ) are essentially unknown. The purpose of this study was to determine the effects of trichostatin A (TSA) and vorinostat (VOR) on functional GJ expression in ventricular cardiomyocytes. The effects of HDAC inhibition on connexin43 (Cx43) expression and functional GJ assembly were examined in primary cultured neonatal mouse ventricular myocytes. TSA and VOR reduced Cx43 mRNA, protein expression, and immunolocalized Cx43 GJ plaque area within ventricular myocyte monolayer cultures in a dose-dependent manner. Chromatin-immunoprecipitation experiments revealed altered protein interactions with the Cx43 promoter. VOR also altered the phosphorylation state of several key regulatory Cx43 phospho-serine sites. Patch clamp analysis revealed reduced electrical coupling between isolated ventricular myocyte pairs, altered transjunctional voltage-dependent inactivation kinetics, and steady state junctional conductance inactivation and recovery relationships. Single GJ channel conductance was reduced to 54 pS only by maximum inhibitory doses of TSA (>= 100 nM). These two hydroxamate pan-HDAC inhibitors exert multiple levels of regulation on ventricular GJ communication by altering Cx43 expression, GJ area, post-translational modifications (e.g. phosphorylation, acetylation), gating, and channel conductance. Although a 50% downregulation of Cx43 GJ communication alone may not be sufficient to slow ventricular conduction or induce arrhythmias, the development of class-selective HDAC inhibitors may help avoid the potential negative cardiovascular effects of pan-HDACI.